Reading between the lines : integrated language and literature activities - McRae, John.; Boardman, Roy. (Cambridge : New York : Cambridge University Press, 1984)
This book contains a wide range of texts with related exercises which aim to make literature more accessible while developing general fluency.
Keywords: Readers (Secondary).; English language -- Textbooks for foreign speakers